PEMBUATAN MOSQUITO TRAP (PERANGKAP NYAMUK) HERBAL DESA DUDUK SAMPEYAN KECAMATAN DUDUK SAMPEYAN KABUPATEN/KOTA GRESIK - Dwi Aprilia Anggraini; Norma Farizah Fahmi (STIKES NGUDIA HUSADA MADURA, 2023)
Dengue fever or dengue hemorrhagic fever (DHF) is a disease caused by infection with the dengue virus. This virus enters the human body through the bite of the Aedes aegypti and Aedes albopictus mosquitoes, which live in tropical and subtropical regions. It is estimated that there are at least 50 million cases of dengue fever worldwide each year. According to data compiled by the Ministry of Health of the Republic of Indonesia, dengue fever has been an endemic disease in Indonesia since 1968. Since then, this disease has become one of the main problems in Indonesia, with the spread and number of sufferers tending to increase every year. Throughout 2017, it is known that there were around 59,000 cases of dengue fever throughout Indonesia, with more than 400 cases of which ended in death. Due to the large population, the Provinces of Central Java and East Java contributed the most cases of DHF for 2017, which was more than 7000 cases in each province. Mosquito traps are simple mosquito traps made of mineral water plastic cups or mineral water bottles filled with a coffee solution and lemongrass slices as an ingredient to attract mosquitoes. Mosquito traps are ready to be used for 10 to 14 days and placed in places where there are suspected to be a lot of mosquitoes. Based on the results of community service in your village, it is known that 40 people are very enthusiastic about the Mosquito trap program by providing several examples of mosquito traps through PKK and Posyandu women. So the main focus in maintaining cleanliness in the family is to provide knowledge to a mother as the implementation of the 3M movement in the family, namely by maintaining a good home environment for her family, implementing the 3M movement simultaneously.